The burden and trends of gastric cancer from 1990 to 2021 in China and globally: a cross-sectional study - Yin, Yulai; Zhang, Xiaoyu (Frontiers in Medicine, 2025)
ObjectiveThis study aimed to systematically analyze the trends in gastric cancer burden in China and globally from 1990 to 2021 using data from the Global Burden of Disease (GBD) database, and to forecast future trends from 2022 to 2036. The findings provide a scientific basis for developing targeted gastric cancer prevention and control policies.MethodsAge-standardized incidence rates (ASIR) and age-standardized mortality rates (ASMR) for gastric cancer from 1990 to 2021 were extracted from the GBD database. These data were complemented by GLOBOCAN 2022 statistics to analyze the spatiotemporal characteristics of gastric cancer burden across time, sex, and regions. An autoregressive integrated moving average (ARIMA) model was employed to predict trends from 2022 to 2036.ResultsFrom 1990 to 2021, both ASIR and ASMR for gastric cancer demonstrated significant declines in China and globally. In China, the ASIR decreased from 70.458 per 100,000 in 1990 to 40.125 per 100,000 in 2021 and is projected to further decrease to 25.432 per 100,000 by 2036. Similarly, the ASMR declined from 60.781 per 100,000 in 1990 to 30.214 per 100,000 in 2021 and is forecasted to reach 18.673 per 100,000 by 2036. Globally, the ASIR fell from 35.284 per 100,000 in 1990 to 20.157 per 100,000 in 2021, with a predicted decrease to 12.493 per 100,000 by 2036. Meanwhile, the global ASMR dropped from 30.651 per 100,000 in 1990 to 15.372 per 100,000 in 2021 and is expected to reach 10.284 per 100,000 by 2036. The study also identified significant gender disparities, with males experiencing a substantially higher burden of gastric cancer than females in both China and globally. Furthermore, the age of peak incidence gradually shifted to older age groups, and high-income regions exhibited greater declines in gastric cancer burden compared to low-income regions, highlighting notable regional disparities.ConclusionOver the past three decades, significant progress has been made in reducing the burden of gastric cancer in China and globally, with declining incidence and mortality rates. These trends are expected to continue in the coming years. However, low-and middle-income countries have seen more limited reductions, with some regions even experiencing increasing burdens. The findings underscore the need for enhanced public health policies focused on preventing Helicobacter pylori infections, promoting healthy dietary and lifestyle changes, and expanding the coverage of early screening programs. This study provides critical evidence to support the optimization of global and regional gastric cancer prevention and control strategies.